HUBUNGAN MANAJEMEN WAKTU DENGAN PRODUKTIVITAS KERJA PERAWAT PELAKSANA DI RUMAH SAKIT UMUM DAERAH TOBELO KABUPATEN HALMAHERA UTARA - Budo, Kesya (Journal Of Community & Emergency, 2024)
The work productivity of a nurse can be seen from the quality of nursing care provided to patients and quality nursing care needs to be oriented to better patient outcomes, this condition can be achieved if supported by adequate human resources in quality and quantity. The implementation of nursing care that is documented in the client's medical record is one of the descriptions of the condition of the nurse's performance in carrying out her duties and work. Time discipline determines the quality of work in the priority of nursing services. Timeliness in providing nursing services is the responsibility of the nurse's performance. The aspect of working time is related to the allocation of time used to carry out their duties every day. The research objective is to know the relationship between time management and work productivity of implementing nurses at the Tobelo Regional General Hospital, North Halmahera Regency. The type of research is descriptive analytic, the research time is in September 2021 and the research location is at the Tobelo Regional General Hospital, North Halmahera Regency. The statistical test used is Chi Square with a 95% confidence degree if . The results showed that Ha was accepted and Ho was rejected, which means there is a value of -value = 0.002 which is smaller than the value of = 0.05. It means that H0 is rejected, then there is a significant relationship between time management and work productivity of implementing nurses at Tobelo Hospital, North Halmahera Regency. The conclusion in this study is that the time management of nurses in Tobelo Hospital, North Halmahera Regency has more good time management than less time management. The work productivity of implementing nurses at Tobelo Hospital, North Halmahera Regency is more good work productivity compared to less work productivity. Suggestions in this study provide input for the hospital and can optimize existing time management, so that the Work Productivity of Implementing Nurses can be increased and the health program objectives are successful.